Israel vs. Iran the shadow war - Katz, Yaakov 1979-
Drawing on in-depth research and invaluable access to the Israeli defense establishment, including interviews with key decision makers, Israeli military correspondent Yaakov Katz and Israeli military historian Yoaz Hendel describe behind-the-scenes Israeli strategic military deliberations and intelligence analysis since the Second Lebanon War of 2006. The authors focus on pivotal military events in this shadow war with Iran, including the Syrian reactor bombing and Operation Cast Lead in the Gaza Strip, as well as assassinations of key Hezbollah operatives, Iranian nuclear scientists, and Syrian officials.